Using Isotopic Tools to Dissect and Quantitate Parallel Metabolic Pathways - Sadhukhan, Sushabhan (2010)
4-hydroxyacids are ubiquitous in human physiology. They are derived from the drugs of abuse γ-hydroxybutyrate (GHB), γ-hydroxypentanoate(GHP), in addition to the omnipresent lipid peroxidation product 4-Hydroxy-2-(E)-nonenal (4-HNE). Previously we reported that 4-hydroxyacids are catabolized through two parallel pathways. In this report we detail two isotopic tools that have allowed the dissection of this catabolic process, and illustrate how these tools can be used to quantify the relative flux down each pathway. We found that 4-hydroxynonanoate (a 4-hydroxyacid derived from 4-HNE) is primarly catabolized through a pathway that phosphorylates the C-4 hydroxyl and isomerizes it to a C-3 hydroxy compound, which is catabolized through β-oxidation.